Blood flow restricted exercise for athletes: A review of available evidence - Scott, B. R.; Loenneke, J. P.; Slattery, K. M.; Dascombe, B. J. (Journal of Science and Medicine in Sport, 2016)
Objectives: This study aimed to collate current evidence regarding the efficacy of various blood flow restriction (BFR) strategies for well-trained athletes, and to provide insight regarding how such strategies can be used by these populations. Design: Review article. Methods: Studies that had investigated the acute or adaptive responses to BFR interventions in athletic participants were identified from searches in MEDLINE (PubMed), SPORTDiscus (EBSCO) and Google Scholar databases up to April 2015. The reference lists of identified papers were also examined for relevant studies. Results: Twelve papers were identified from 11 separate investigations that had assessed acute and adaptive responses to BFR in athletic cohorts. Of these, 7 papers observed enhanced hypertrophic and/or strength responses and 2 reported alterations in the acute responses to low-load resistance exercise when combined with BFR. One paper had examined the adaptive responses to moderate-load resistance training with BFR, 1 noted improved training responses to low-work rate BFR cardiovascular exercise, and 1 reported on a case of injury following BFR exercise in an athlete. Conclusions: Current evidence suggests that low-load resistance training with BFR can enhance muscle hypertrophy and strength in well-trained athletes, who would not normally benefit from using light loads. For healthy athletes, low-load BFR resistance training performed in conjunction with normal high-load training may provide an additional stimulus for muscular development. As low-load BFR resistance exercise does not appear to cause measureable muscle damage, supplementing normal high-load training using this novel strategy may elicit beneficial muscular responses in healthy athletes.